2021
DOI: 10.1097/cnd.0000000000000341
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Small Fiber Neuropathy Associated With Ehlers–Danlos Syndrome Treated With Intravenous Immunoglobulins

Abstract: Patients with Ehlers–Danlos syndrome (EDS) have many associated symptoms of unclear cause, most recently suggested to be due to small fiber neuropathy (SFN). Small fiber neuropathies are sorely underestimated and with minimal treatment options. We report 2 cases of patients with EDS with presumed immune-mediated SFN, successfully treated with IV immunoglobulins. There is a stark need for further investigational studies into immunosuppressant treatments for immune-mediated SFN as well as the link between EDS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…5 In a study of two patients with Ehlers-Danlos syndrome, immune-mediated SFN was suspected and successfully treated with IVIG. 77 In a 32-year-old man carrying an SCN9A variant, clinical manifestations of SFN (disabling exertional intolerance ("chronic fatigue syndrome"), POTS, arm and leg paresthesias, reduced sweating, and distal hair loss) improved upon IVIG. 78 In a 47-year-old man with biopsy-proven SFN manifesting with disabling neuropathic pain and exercise intolerance, whole-exome sequencing revealed the variant c.3734A>G in SCN9A.…”
Section: Immunoglobulinsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In a study of two patients with Ehlers-Danlos syndrome, immune-mediated SFN was suspected and successfully treated with IVIG. 77 In a 32-year-old man carrying an SCN9A variant, clinical manifestations of SFN (disabling exertional intolerance ("chronic fatigue syndrome"), POTS, arm and leg paresthesias, reduced sweating, and distal hair loss) improved upon IVIG. 78 In a 47-year-old man with biopsy-proven SFN manifesting with disabling neuropathic pain and exercise intolerance, whole-exome sequencing revealed the variant c.3734A>G in SCN9A.…”
Section: Immunoglobulinsmentioning
confidence: 99%
“…In another study of idiopathic SFN with IVIG, no significant therapeutic benefit could be documented, why it was concluded that the use of IVIG for idiopathic SFN should be discouraged 5 . In a study of two patients with Ehlers‐Danlos syndrome, immune‐mediated SFN was suspected and successfully treated with IVIG 77 . In a 32‐year‐old man carrying an SCN9A variant, clinical manifestations of SFN (disabling exertional intolerance ("chronic fatigue syndrome"), POTS, arm and leg paresthesias, reduced sweating, and distal hair loss) improved upon IVIG 78 .…”
Section: Treatmentmentioning
confidence: 99%